1989
DOI: 10.1007/bf01759579
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical responses to therapy in Alzheimer's disease and multi-infarct dementia

Abstract: Memory performance, central monoaminergic function and sympathetic nerve activity were studied in patients with dementia of the Alzheimer type (DAT) or with multi-infarct dementia before and after 4 weeks with single or combined drug therapy (choline-piracetam). Analysis of the levels of 3-methoxy-4-hydroxyphenylglycol (MHPG), 3-methoxy-4-hydroxyphenylacetic acid (HVA) and 5-hydroxyindolacetic acid in the cerebrospinal fluid (CSF) and also in urine (plus 3-methoxy-4-hydroxy mandelic acid) showed that the basal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…This notion is consistent with the finding that CSF levels of HVA are similar in patients with Parkinson's disease and demented patients with extrapyramidal features 50 . Similarity of CSF HVA in AD patients and patients with multi‐infarct dementia (MID) 41 , 47 , 51 also argues against the specificity of the HVA reduction in AD. Zubenko et al 33 even found an increase of HVA in CSF from patients with only a mild degree of dementia.…”
Section: Classical Neurotransmitter Systemssupporting
confidence: 86%
See 4 more Smart Citations
“…This notion is consistent with the finding that CSF levels of HVA are similar in patients with Parkinson's disease and demented patients with extrapyramidal features 50 . Similarity of CSF HVA in AD patients and patients with multi‐infarct dementia (MID) 41 , 47 , 51 also argues against the specificity of the HVA reduction in AD. Zubenko et al 33 even found an increase of HVA in CSF from patients with only a mild degree of dementia.…”
Section: Classical Neurotransmitter Systemssupporting
confidence: 86%
“…Interpretation of this finding is difficult because it has not been reproduced by other groups as yet. The same holds true for reports on reduction of dopamine‐β‐hydroxylase activity in CSF of AD patients 42–56 …”
Section: Classical Neurotransmitter Systemssupporting
confidence: 52%
See 3 more Smart Citations